Conditions of Perfect Imaging in Negative Refraction Materials with Gain. (8th November 2012) - Liang, Haowen; Shao, Yifeng; Zhou, Jianying; Malomed, Boris A.; Kurizki, Gershon
Abstract : Light propagation is analyzed in a negative refraction material (NRM) with gain achieved by pumping. An inherent spatial "walk-off" between the directions of phase propagation and energy transfer is known to exist in lossy NRMs. Here, the analysis is extended to the case where the NRM acts as an active material under various pumping conditions. It is shown that the condition for perfect imaging is only possible for specific wavelengths under special excitation conditions. Under excessive gain, the optical imaging can no longer be perfect.